2014
DOI: 10.3389/fnhum.2014.00418
|View full text |Cite
|
Sign up to set email alerts
|

Manual choice reaction times in the rate-domain

Abstract: Over the last 150 years, human manual reaction times (RTs) have been recorded countless times. Yet, our understanding of them remains remarkably poor. RTs are highly variable with positively skewed frequency distributions, often modeled as an inverse Gaussian distribution reflecting a stochastic rise to threshold (diffusion process). However, latency distributions of saccades are very close to the reciprocal Normal, suggesting that “rate” (reciprocal RT) may be the more fundamental variable. We explored whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Additional problems were caused by some extreme outlier values. Similarly, other transformations considered by Harris et al (2014) did not lead to satisfactory results in this case.…”
Section: Resultssupporting
confidence: 41%
See 1 more Smart Citation
“…Additional problems were caused by some extreme outlier values. Similarly, other transformations considered by Harris et al (2014) did not lead to satisfactory results in this case.…”
Section: Resultssupporting
confidence: 41%
“…According to Harris et al (2014) RT experiments have become a standard paradigm for measuring behavioral reactions without taking into account underlying mental processes. Harris et al (2014) suggested a sophisticated way to improve the analysis and interpretations of RT paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…First, raw RT data were transformed using a reciprocal transform [see ( 25 )]. For basic analyses, mean reciprocal RTs from correct trials were calculated for each cue (high/medium/low) and block (first/second) separately.…”
Section: Methodsmentioning
confidence: 99%
“…As a follow up analysis, reciprocal RTs from the whole task (both blocks) were fit within a single general linear model [GLM: ( 25 , 27 )] separately for each participant. The goal of this modeling was broadly to demonstrate that the data are consistent with a Reinforcement Learning (RL) model, and that similar findings could be obtained using different modeling approaches.…”
Section: Methodsmentioning
confidence: 99%
“…In a different type of analysis, the work of Harris et al introduces an alternative approach to examine very long RTs in the rate-domain (i.e., 1/RT). These authors investigate the shape of choice RT distributions and sequential correlations using autoregressive techniques (Harris et al, 2014). In general, RT distributions exhibit faster RTs under summation/facilitation tasks when two or more redundant signals are available as compared with a single signal or sensory modality (e.g., binocular vs. monocular vision), usually called redundant signals effect.…”
mentioning
confidence: 99%